Kedudukan Teori Ilmu Manajemen dan Menganalisa Teori Manajemen Pendidikan - Panggita, Fairuza Setya Eka; Setiadi, Deni (Journal of Educational Review and Cultural Studies, 2024)
Management theory has undergone rapid development, encompassing various approaches to enhance organizational efficiency and effectiveness. This article explores the evolution of management theories, including contributions from Muslim scholars such as Ibn Khaldun with the concept of asabiyyah (social solidarity), which is relevant for building a collaborative work culture. Management is defined as the process of planning, organizing, directing, and controlling resources to achieve organizational goals.The study discusses theories such as Scientific Management, Modern Management, General Administrative Management, as well as quantitative and behavioral approaches. Furthermore, the position of knowledge in Islam is presented as an ontological foundation connecting physical and metaphysical existence, with God as the ultimate source of all being.This article also highlights the future directions of management theory through five main perspectives: Dominance, Divergence, Convergence, Synthesis, and Proliferation. The conclusion emphasizes the importance of integrating traditional and modern management principles to address organizational challenges sustainably.